2020
DOI: 10.36660/abc.20190282
|View full text |Cite
|
Sign up to set email alerts
|

Um Olhar sobre o Stress nas Mulheres com Infarto Agudo do Miocárdio

Abstract: Fundamento: As mulheres parecem ser mais suscetíveis ao estresse psicossocial quando comparadas aos homens, e o estresse está associado a piora na evolução clínica dos pacientes após o infarto agudo do miocárdio (IAM). Objetivos: Investigar se o sexo feminino é preditor independente de risco para o estresse e comparar os níveis de estresse entre mulheres e homens com IAM. Métodos: Estudo transversal de uma série de casos, realizado entre janeiro de 2017 e junho de 2018. Pacientes com idade entre 18 e 65 anos, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 24 publications
1
4
0
4
Order By: Relevance
“…The findings on significant differences in stress as a function of participant gender replicate findings in the literature (Viertiö et al, 2021). Although women and men share many particularly stressful situations in everyday life (financial conditions, job security, relationship problems), stress symptoms are more prevalent and intense in women (Lipp & Lipp, 2020;Schmidt et al, 2020).…”
Section: Discussionsupporting
confidence: 68%
“…The findings on significant differences in stress as a function of participant gender replicate findings in the literature (Viertiö et al, 2021). Although women and men share many particularly stressful situations in everyday life (financial conditions, job security, relationship problems), stress symptoms are more prevalent and intense in women (Lipp & Lipp, 2020;Schmidt et al, 2020).…”
Section: Discussionsupporting
confidence: 68%
“…This study found a higher prevalence of grades I and II angina in women, which can be explained by the greater exposure of this group to stress 14 , in addition to the fact that men usually present different clinical pictures in coronary heart disease such as acute infarction and sudden death 15 .…”
Section: Discussionmentioning
confidence: 57%
“…29,30 Women are also more susceptible to psychosocial stress than men, and stress is associated with worse outcomes after AMI. 31 Further studies are needed to understand the worse clinical outcomes after AMI in women.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Women are also more susceptible to psychosocial stress than men, and stress is associated with worse outcomes after AMI. 31…”
Section: Gender Differencesmentioning
confidence: 99%